2008
DOI: 10.3322/ca.2007.0016
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Extradural Metastasis: Review of Current Treatment Options

Abstract: Bone metastases, especially to the spine, are frequently encountered during the course of a malignancy. Due to a worldwide increase of cancer incidence and to a longer life expectancy of patients with cancer, a rise in incidence of bone metastases is observed. A brief historical overview is the base of a review of current treatment options. Despite new developments in the surgical and radiotherapeutic fields, as well as in medical oncology, external beam radiotherapy is the cornerstone of the treatment of spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
145
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(155 citation statements)
references
References 162 publications
2
145
1
7
Order By: Relevance
“…In stratified analysis, adjusted for age, gender, N stage, KPS, spine involvement, and more than three or three or fewer metastatic sites, we found that combined CRT may [31][32][33], this preliminary finding suggested that a considerable proportion of patients with single bone metastasis receiving combined CRT could be cured. Future match-paired or even prospective studies are warranted to validate this finding.…”
Section: Cmementioning
confidence: 70%
“…In stratified analysis, adjusted for age, gender, N stage, KPS, spine involvement, and more than three or three or fewer metastatic sites, we found that combined CRT may [31][32][33], this preliminary finding suggested that a considerable proportion of patients with single bone metastasis receiving combined CRT could be cured. Future match-paired or even prospective studies are warranted to validate this finding.…”
Section: Cmementioning
confidence: 70%
“…The prediction for survival is, for example, important to choose between long-or short-course radiotherapy [14]. The predicted survival apart from other factors also determines whether a patient will be a surgical candidate [1].…”
Section: Discussionmentioning
confidence: 99%
“…New insights contributed to this development. To be a surgical candidate, an expected survival of at least 3 months apart from other factors is mandatory [1].…”
Section: Introductionmentioning
confidence: 99%
“…96 Common treatment options for patients with metastatic skin malignancies include surgical excision, radiotherapy, chemotherapy, immunotherapies, small molecule inhibitors, steroids, and analgesics. 12,50 The majority of patients diagnosed with a metastasis from skin malignancy often receive palliative treatment, given the poor prognoses at this stage of disease. For patients with spinal metastases, surgical intervention is considered in cases of mechanical instability, tumor progression during radiation therapy or failed radiation, medically intractable pain, and/or functionally significant or progressive neurological dysfunction.…”
mentioning
confidence: 99%